Optimization planning of a construction of a front wall gondola wagon model 12-9745 by minimum materials consumption criterion - Мороз, Володимир Ілліч; Братченко, Олександр Васильович; Фомін, Олексій Вікторович (Eastern-European Journal of Enterprise Technologies, 2010)
In the article the represented features and results of the optimising planning of a construction of a front wall gondola wagon model 12-9745 by minimum materials consumption criterion.